2013
DOI: 10.1155/2013/857937
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of Rayleigh Wave in a Two-Temperature Generalized Thermoelastic Solid Half-Space

Abstract: The Rayleigh surface wave is studied at a stress-free thermally insulated surface of an isotropic, linear, and homogeneous twotemperature thermoelastic solid half-space in the context of Lord and Shulman theory of generalized thermoelasticity. The governing equations of a two-temperature generalized thermoelastic medium are solved for surface wave solutions. The appropriate particular solutions are applied to the required boundary conditions to obtain the frequency equation of the Rayleigh wave. Some special c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 25 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Later on, Youssef and Al-Lehaibi [24], Misra et al [25], Singh [26], and Singh and Bala [27] investigated various problems on the basis of two temperature thermoelasticity with relaxation times and showed that the obtained results are qualitatively different as compared to those in case of one temperature thermoelasticity.…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
“…Later on, Youssef and Al-Lehaibi [24], Misra et al [25], Singh [26], and Singh and Bala [27] investigated various problems on the basis of two temperature thermoelasticity with relaxation times and showed that the obtained results are qualitatively different as compared to those in case of one temperature thermoelasticity.…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
“…Kumar and Mukhopadhay [9] studied the effects of thermal relaxations on wave propagation in theory of two-temperature thermoelasticity. Singh [17] studied the Rayleigh surface wave at a stress free thermally insulated surface of an isotropic, linear, and homogeneous two-temperature thermoelastic solid half-space in the context of Lord and Shulman theory of generalized thermoelasticity.…”
mentioning
confidence: 99%